Peran Gen Polimorfik δ Asam Amino Levulinat Dehidratase pada Intoksikasi Pb - Henna Rya Sunoko (MEDIA MEDIKA INDONESIANA, 2008)
ABSTRACTThe role of δ amino levulinic acid dehydratase polymorphism gene in lead intoxication.Background: Three distinct isozymes, designated ALAD 1-1, 1-2, and 2-2 are resulted from the expression of two common alleles, designated ALAD1 and ALAD2. The existence of this polymorphism gene whose product was implicated in the pathogenesis of lead toxicity suggested the potential for a genetically determined differential susceptibility. This study was attempted to investigate the role of ALAD polymorphism gene in lead intoxication showed by children blood lead levels.Methods: The study involved 54 children with 5-10-year-old, coming from Gebang Sari, Sekaran and Moro Demak. Cross-sectional design was adopted in this research. Blood lead level was measured by atomic absorption spectrophotometer. The ALAD polymorphism in exon 4 was determined by polymerase chain reaction (PCR) with restriction fragment length polymorphism, according to the methods described by Schwartz et al. Data were not statistically analyzed due to only two samples were ALAD2.Results: Two samples were ALAD2 (1-2 isozymes) with blood lead levels (BLL) of 24.50 ppb and 91.70 ppb respectivelly. The mean of ALAD2 BLL was about 48.60 ppb higher compared to that of ALAD1BLL.Conclusion: Individuals with ALAD2genotype had blood lead levels higher than those of individuals with the ALAD1 genotype, therefore, ALAD2genotype was much more susceptible to lead .Key Words: ALAD polymorphism gene, ALAD1, ALAD2, blood lead levelABSTRAKLatar belakang: ALAD 1-1, 1-2, dan 2-2, adalah tiga isozym yang berasal dari dua macam alel yaitu ALAD1 dan ALAD2. Keberadaan gen ALAD polimorfik dengan produknya ini, dalam patogenesis toksisitas Pb telah mengimplikasikan bahwa secara genetik sangat potensial untuk menyebabkan terjadinya perbedaan suseptabilitas terhadap Pb. Penelitian ini ditujukan untuk mempelajari peran gen ALAD polimorfik pada intoksikasi Pb yang ditunjukkan oleh tingkat kadar Pb darah.Metode: Penelitian mengikutsertakan 54 anak, umur 5-10 tahun, berasal dari Gebang Sari, Sekaran dan Moro Demak. Penelitian didesain secara cross-sectional. Kadar Pb darah diukur dengan alat atomic absorption spectrophotometer. ALAD polimorfik pada exon 4 dideterminasi dengan polymerase chain reaction (PCR) dengan restriksi “fragmentlength polymorphism” sesuai dengan metoda Schwartz et al. Analisis statistik tidak dilakukan sebab hanya ada dua sampel dengan ALAD2.Hasil: Ditemukan dua sampel anak dengan ALAD2 (1-2 isozymes), kadar Pb darah masing-masing 24,50 ppb dan 91,70 ppb. Rerata kadar Pb darah dengan ALAD2 lebih tinggi sekitar 48,60 ppb dibanding rerata kadar Pb darah dengan ALAD1.Simpulan: Genotipe ALAD2 lebih suseptibel terhadap Pb.